2018
DOI: 10.1016/j.jhevol.2018.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Dental topography and the diet of Homo naledi

Abstract: Though late Middle Pleistocene in age, Homo naledi is characterized by a mosaic of Australopithecus-like (e.g., curved fingers, small brains) and Homo-like (e.g., elongated lower limbs) traits, which may suggest it occupied a unique ecological niche. Ecological reconstructions inform on niche occupation, and are particularly successful when using dental material. Tooth shape (via dental topography) and size were quantified for four groups of South African Plio-Pleistocene hominins (specimens of Australopithecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 96 publications
(192 reference statements)
3
100
0
1
Order By: Relevance
“…Again, in the light of our findings this would make a dust‐loaded diet unlikely but rather suggests that this microwear signature was the result of small sized seeds. However, we cannot fully exclude the possibility that grit (sensu stricto—coarse sand with a grain size of 0.5–2 mm) caused these chips and was also involved in texture formation as suggested by Towle, Irish, and De Groote () and Berthaume, Delezene, and Kupczik (). Both fossil hominin examples show that more field observations and feeding experiments under controlled conditions are needed to better understand texture formation.…”
Section: Discussionmentioning
confidence: 82%
“…Again, in the light of our findings this would make a dust‐loaded diet unlikely but rather suggests that this microwear signature was the result of small sized seeds. However, we cannot fully exclude the possibility that grit (sensu stricto—coarse sand with a grain size of 0.5–2 mm) caused these chips and was also involved in texture formation as suggested by Towle, Irish, and De Groote () and Berthaume, Delezene, and Kupczik (). Both fossil hominin examples show that more field observations and feeding experiments under controlled conditions are needed to better understand texture formation.…”
Section: Discussionmentioning
confidence: 82%
“…It has recently been suggested that the Middle Pleistocene Cave of Hearths mandible, which has been assigned to H. sapiens rhodesiensis (Tobias, 1971), could belong to H. naledi (Berger et al, 2017). However, this is unlikely given that the Cave of Hearths mandible differs from the latter in several dental morphological features including occlusal topography of the M2 (Berthaume et al, 2018), overall premolar and molar crown morphology (L.K.D., pers. obs.)…”
Section: Discussionmentioning
confidence: 99%
“…ArcGIS (Esri, Redlands, CA) is a GIS software package that can measure or provide input measures for OR, m , and a (e.g., Dennis et al, ; M'Kirera & Ungar, ; Ungar et al, ; Ungar & M'Kirera, ; Ungar & Williamson, ; Zuccotti et al, ). MorphoTester (Winchester, ), calculates OPCR, DNE, and OR (see Berthaume, ; Berthaume, Delezene & Kupczik, ; Berthaume & Schroer, ; Polivka, ; Prufrock, Boyer & Silcox, ). Finally, molaR, an R package capable of calculating OPCR, DNE, m , and OR (Pampush et al, ) has been employed in a number of dental topography studies (e.g., Harper, Parras & Rougier, in press; Pampush et al, , ; Peredo, Peredo & Pyenson, ; Renaud & Ledevin, ; Renaud et al, ).…”
Section: Introductionmentioning
confidence: 99%